2009
DOI: 10.1007/s12187-009-9059-1
|View full text |Cite
|
Sign up to set email alerts
|

Family Structure and Children’s Living Conditions. A Comparative Study of 24 Countries

Abstract: This study uses large-scale cross-national data from 24 countries to describe the living conditions of children residing with a single mother as compared with children who live with two original parents. Three central areas are studied: children's social support, health, and material resources. The data are derived from the international WHO study Health Behaviour in School-aged Children (HBSC) of 2001/02. The survey includes nationally representative samples of school pupils of 11, 13, and 15 years of age in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…For instance, Laftman (2010) found that when it comes to the description of one's household as not satisfactory or "not well off" children in single-mother households tend to report this more often than their peers living with two original parents. One fundamental difference between two-parent and single-mother families has been found to be related to the economy of the households (Laftman, 2010). According to McLanahan (2008), the single most important factor contributing to difficulties or unsatisfactory experiences by children in single-mother households is the low family income.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, Laftman (2010) found that when it comes to the description of one's household as not satisfactory or "not well off" children in single-mother households tend to report this more often than their peers living with two original parents. One fundamental difference between two-parent and single-mother families has been found to be related to the economy of the households (Laftman, 2010). According to McLanahan (2008), the single most important factor contributing to difficulties or unsatisfactory experiences by children in single-mother households is the low family income.…”
Section: Discussionmentioning
confidence: 99%
“…Poor financial resource is responsible for single-mother households being located in small residences, backyard dwellings,substandard housing and in the areas of town with increased violence, lower quality schools and loss of familiar and developed community support, all of which negatively impact children's physical, psychological and social well-being (McLanahan, 2008). The general contention by Laftman (2010) is that unsatisfactory financial status of family is likely to contribute to poor subjective well-being or overall dissatisfaction with life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations